Hydrological drought analysis in Continental Temperate and Mediterranean environment during the period 1981-2017 - Falzoi, Simone; Acquaotta, Fiorella; Pulina, Maria Antonia; Fratianni, Simona (Italian Journal of Agrometeorology, 2019)
A 37 year (1981-2017) study of the hydrological drought trend was conducted in two Italian regions, Piedmont and Sardinia, with different climatic features (Temperate Continental climate and Mediterranean climate, respectively). For this purpose, we have examined the daily data of 13 meteorological stations uniformly installed in the two areas, and the trends of the Standardised Precipitation Index (SPI) and Standardised Precipitation Evapotranspiration Index (SPEI) have been also evaluated. The similarities and differences between the indices of the two regions were then considered. In most stations of both zones, there is a statistically significant trend of increase in the SPI and decrease in the SPEI. Nevertheless, the trend of indices averaged over stations of the two indices is not significant in either of the two climatic zones considered.